Microcontroller-based Control and Data Acquisition System for a Grid-connected Renewable Energy System - Kevin D. Dugay; Adam Z. Luisaga; Jomille Angelo Carlo O. Bancud (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
There has been a significant increase in the exploitation of renewable energy systems. To be able to efficiently utilize grid - connected renewable energy sources, there must be a reliable control and monitoring system. In building a control and monitoring system for this system, a power analyzer connected to a microcontroller was used. The microcontroller was linked to touchscreen display where a graphical user interface (GUI) was programmed to able to display and log the data recovered. Relays were used to reconfigure the system by shifting the load’s source of energy between the grid and renewable energy system. The energy generated by the renewable energy system may be delivered to the load or be fed to the grid as needed. This operation will be done through either an external device or through a computer which was built to manually operate the control system and view the status of the system as determined by parameters such as cost and energy consumption. This system provided residential buildings with their own renewable energy system with a simple yet reliable control and monitoring system. The system was able to accumulate accurate and real time data. It also provided a continuous supply and switching application simultaneously.